2016
DOI: 10.1109/jphotov.2015.2496864
|View full text |Cite
|
Sign up to set email alerts
|

Rear Surface Optimization of CZTS Solar Cells by Use of a Passivation Layer With Nanosized Point Openings

Abstract: Previously, an innovative way to reduce rear interface recombination in Cu(In,Ga)(S,Se) 2 (CIGSSe) solar cells has been successfully developed. In this work, this concept is established in Cu 2 (Zn,Sn)(S,Se) 4 (CZTSSe) cells to demonstrate its potential for other thin-film technologies. Therefore, ultrathin CZTS cells with an Al 2 O 3 rear surface passivation layer having nanosized point openings are fabricated. The results indicate that introducing such a passivation layer can have a positive impact on open-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 24 publications
2
45
0
Order By: Relevance
“…This might be due to the reduction of the decomposition reactions at the rear interface by introducing MoO 3 layer and improving the rear surface quality. Several studies have already reported the instability of Mo during the selenization/sulfurization process that leads to the formation of voids, and secondary phases and introduce defects such as Se vacancies . Another hypothesis could be the role of oxygen in passivation of defects, as in high temperature processing the oxygen can be released and fill the different vacancies.…”
Section: Resultsmentioning
confidence: 99%
“…This might be due to the reduction of the decomposition reactions at the rear interface by introducing MoO 3 layer and improving the rear surface quality. Several studies have already reported the instability of Mo during the selenization/sulfurization process that leads to the formation of voids, and secondary phases and introduce defects such as Se vacancies . Another hypothesis could be the role of oxygen in passivation of defects, as in high temperature processing the oxygen can be released and fill the different vacancies.…”
Section: Resultsmentioning
confidence: 99%
“…[15][16][17][18] Such passivation layer can lead to three advantageous effects: (i) chemical passivation; (ii) field effect passivation; (iii) increased reflection at the rear contact; all while maintaining good electrical contact and devices with high values of fill factor. [15][16][17][18] Such passivation layer can lead to three advantageous effects: (i) chemical passivation; (ii) field effect passivation; (iii) increased reflection at the rear contact; all while maintaining good electrical contact and devices with high values of fill factor.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the rear interface can be effectively passivated by an Al 2 O 3 nanopatterned layer forming a point contact structure. [15][16][17][18] Such passivation layer can lead to three advantageous effects: (i) chemical passivation; (ii) field effect passivation; (iii) increased reflection at the rear contact; all while maintaining good electrical contact and devices with high values of fill factor. Chemical passivation, a terminology coming from the silicon technology, is simply related with a reduction on the interface defect density and it is still an electronic effect.…”
Section: Introductionmentioning
confidence: 99%
“…Afterwards, a physical etching process is performed through the dielectric exposing Mo, allowing for contact of the rear electrode to the CIGS. For this purpose, a reactive ion etching (RIE) process on SPTS ICP is used which according to our experience, does not change the contact properties of the Mo with CIGS . The system is capable of etching deep sub‐micron features with near vertical sidewalls (anisotropic) and provides good selectivity.…”
Section: Summary Of the Samples Produced In This Work As Well The Expmentioning
confidence: 99%